2021
DOI: 10.7554/elife.65068
|View full text |Cite
|
Sign up to set email alerts
|

Human embryo polarization requires PLC signaling to mediate trophectoderm specification

Abstract: Apico-basal polarization of cells within the embryo is critical for the segregation of distinct lineages during mammalian development. Polarized cells become the trophectoderm (TE), which forms the placenta, and apolar cells become the inner cell mass (ICM), the founding population of the fetus. The cellular and molecular mechanisms leading to polarization of the human embryo and its timing during embryogenesis have remained unknown. Here, we show that human embryo polarization occurs in two steps: it begins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…A recent study with supernumerary IVF human embryos at day 4 has determined the sequence of developmental events of human embryo polarization in relation to compaction [ 199 ]. Accordingly, compacted blastomeres display an apical enrichment of cortical F-actin at the cell-contact free surface, along with a slightly time-delayed polarization of the PAR complex components PARD6 and atypical Protein Kinase C (aPKC).…”
Section: Trophoblast Lineage Morphogenesis In the Blastocystmentioning
confidence: 99%
“…A recent study with supernumerary IVF human embryos at day 4 has determined the sequence of developmental events of human embryo polarization in relation to compaction [ 199 ]. Accordingly, compacted blastomeres display an apical enrichment of cortical F-actin at the cell-contact free surface, along with a slightly time-delayed polarization of the PAR complex components PARD6 and atypical Protein Kinase C (aPKC).…”
Section: Trophoblast Lineage Morphogenesis In the Blastocystmentioning
confidence: 99%
“…We have previously shown that morula stage mouse, cow, and human embryos, acquire an apical-basal cell polarity in outer cells, with expression of aPKC localized to the contact-free domain, nuclear expression of the Hippo pathway downstream effectors YAP1 and WWTR1, and restricted expression of TE-associated factors such as GATA3, suggesting conservation of the initiation of a TE program across these species (Gerri et al, 2020). Furthermore, inhibition of aPKC activity impairs TE initiation at the morula stage in cow and human embryos (Gerri et al, 2020), and downregulation of the polarity regulators Phospholipase CB1 (PLC) and PLCE1 leads to decreased GATA3 expression in human embryos (Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Compaction and establishment of apical polarity marks the initial separation of outer polarized cells that will go on to form the TE and takes place between days 3 and 4 after fertilization in the human (Iwata et al, 2014). A recent study has detailed the dynamics of compaction in the human embryo at the 8-16 cell stage and showed that transmembrane phosphoinositide-specific phospholipase C (PLC) signaling is required for apical domain formation (Zhu et al, 2021). In final form and function, the human blastocyst at embryonic day (E) 6-7, with its three distinct cell lineages, is very similar to the mouse blastocyst, but the detailed mechanisms of lineage commitment may differ.…”
Section: Making the Blastocyst: The Preimplantation Lineagesmentioning
confidence: 99%
“…OCT4, which is a key transcription factor (TF) for ICM formation in mice (Nichols et al, 1998), is broadly expressed in all cells, including both ICM and TE, right up to the expanded blastocyst stage, while CDX2, which is a key regulator of TE initiation in the mouse (Strumpf et al, 2005), is not expressed until after blastocyst formation (Niakan and Eggan, 2013). Other genes involved in TE formation in the mouse, such as Elf5 and Eomes, are not expressed at the blastocyst stage in humans, while GATA3, which plays a subsidiary role in mouse TE formation (Ralston et al, 2010), is expressed in TE precursors in the human embryo (Gerri et al, 2020a;Petropoulos et al, 2016;Zhu et al, 2021).…”
Section: Making the Blastocyst: The Preimplantation Lineagesmentioning
confidence: 99%